Pengembagan Lembar Kerja Peserta Didik (LKPD) Berbasis Kontekstual Teaching and Learning (CTL) Pada Pembelajaran Tematik - Putra, Angga; Damayanti, Putri Surya; Pujiarti, Titi; Nafisa, Nafisa (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
Student worksheets (LKPD) are assignment sheets that must be completed by students in learning which contain instructions, steps and basic competencies to be achieved. This research aims to measure the validity, practicality and effectiveness of Contextual Teaching and Learning-Based Participant Worksheets in Thematic Learning. The research model used is the development of a 4-D (Four D) model, consisting of 4 stages, namely; define, design, develop, and disseminate. The results of this research are in accordance with the assessment of 2 validator experts, namely that student worksheets with a percentage of 85% are categorized as valid, meaning that the LKPD developed is suitable for use. Apart from that, the results of practicality by expert LKPD practitioners with a percentage of 83% were categorized as practical. Furthermore, the effectiveness of the LKPD is said to be effective if it meets the cognitive, affective and psychomotor domains. It can be seen from the cognitive learning results reaching 93%, while the affective learning results are 3 students who are in the very good category with a percentage of 13%. There are 8 students who are in the good category with a percentage of 70. % there are 3 students who are in the quite good category with a percentage of 13%, there is 1 student who is in the need guidance category with a percentage of 4%. Judging from the psychomotor learning results, there are 11 students in the good category with a percentage of 75% and there are 4 students with a fairly good category with a percentage of 25%.